Lymphocyte Cell Count Profile based on Widal Titer On Pediatric Typhoid Fever - Nurmansyah, Dian; Fayumi, Syihab; Nisa, Shalehatun; Puspawati, Puspawati; Sasmitha, Maya; Mudzakkir, Musyirrah; Arsyad, Muhammad (Poltekkes Kemenkes Mataram, 2025)
Typhoid fever remains a significant public health concern in Indonesia, which has the third-highest global case rate, with 350–810 cases per 100,000 people and a fatality rate of 3.1–10.4%, primarily due to delayed diagnosis and treatment. Children aged 5–14 years are most affected, with transmission occurring via contaminated food, water, or poor hygiene. Salmonella typhi invades intestinal immune tissues (Peyer’s patches), triggering responses from T and B lymphocytes, though bacterial endotoxins can suppress bone marrow function, altering leukocyte levels. This study analyzed the relationship between Widal titer and lymphocyte counts in pediatric typhoid patients using a cross-sectional design. Data from 526 patients at Graha Medika Martapura Clinic and Ratu Zalecha Hospital (January 2023–February 2025) were analyzed statistically, with inclusion criteria of Widal titer ≥1/320 and complete blood count results. Results showed 18.8% of patients had elevated lymphocytes, 79.3% had normal levels, and 1.9% exhibited lymphocytopenia. Higher Widal titers (1/640) correlated with lower lymphocyte counts (15.8% elevated vs. 23.0% at 1/320), suggesting immune suppression mediated by IL-6 through specific signaling pathways. Paradoxically, some cases showed lymphocytosis (18.8%), likely due to cytokine-induced immune modulation. Statistical analysis revealed a minimal correlation (R²=0.006), indicating Widal titer explains only 0.6% of lymphocyte variation. These findings demonstrate that while Widal titer has limited predictive value for lymphocyte changes, immune response mechanisms, particularly involving IL-6, play a critical role in typhoid fever's hematological manifestations.